2018
DOI: 10.1038/nrurol.2018.22
|View full text |Cite
|
Sign up to set email alerts
|

Cellular plasticity and the neuroendocrine phenotype in prostate cancer

Abstract: The success of next-generation androgen receptor (AR) pathway inhibitors, such as abiraterone acetate and enzalutamide, in treating prostate cancer has been hampered by the emergence of drug resistance. This acquired drug resistance is driven, in part, by the ability of prostate cancer cells to change their phenotype to adopt AR-independent pathways for growth and survival. Around one-quarter of resistant prostate tumours comprise cells that have undergone cellular reprogramming to become AR-independent and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
325
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 320 publications
(332 citation statements)
references
References 196 publications
7
325
0
Order By: Relevance
“…These cancers almost universally have loss-of-function alterations in RB1 and TP53 and often include amplifications in the MYC family of genes and altered expression of epigenetic regulators (Beltran et al, 2011; Beltran et al, 2016; George et al, 2015; Poirier et al,2015). Further, conversion to a neuroendocrine phenotype has emerged as a mechanism of treatment resistance in prostate and lung cancers (Davies et al, 2018; Oser et al, 2015). Transcriptional profiling of primary human prostate epithelial populations revealed that advanced prostate cancer subtypes vary in their enrichment of a prostate basal stem cell signature with small cell neuroendocrine prostate cancer (SCNPC) being the most stem-like.…”
Section: Introductionmentioning
confidence: 99%
“…These cancers almost universally have loss-of-function alterations in RB1 and TP53 and often include amplifications in the MYC family of genes and altered expression of epigenetic regulators (Beltran et al, 2011; Beltran et al, 2016; George et al, 2015; Poirier et al,2015). Further, conversion to a neuroendocrine phenotype has emerged as a mechanism of treatment resistance in prostate and lung cancers (Davies et al, 2018; Oser et al, 2015). Transcriptional profiling of primary human prostate epithelial populations revealed that advanced prostate cancer subtypes vary in their enrichment of a prostate basal stem cell signature with small cell neuroendocrine prostate cancer (SCNPC) being the most stem-like.…”
Section: Introductionmentioning
confidence: 99%
“…NEPCs are instead characterized by immunoreactivity to clinical neuroendocrine (NE) markers such as chromogranin A, synaptophysin, CD56, and neuron-specific enolase (NSE), although these are not specific. At the molecular level, these tumors are often characterized by RB1 and PTEN losses and TP53 mutations or deficiencies, which have been associated in preclinical studies with androgen independence [8, 12, 13], as well as increased expression/activity of aurora kinase A and N-Myc [6, 14, 15]. Therefore, while most castration-resistant adenocarcinomas (adeno-CRPCs) remain dependent on AR signaling [16], clinical and preclinical data support the androgen-independence of NEPCs [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…4 As resistance also occurs frequently applying these drugs, it remains necessary to develop novel therapeutic options. 4 As resistance also occurs frequently applying these drugs, it remains necessary to develop novel therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, the key risk factors for PCa occurrence and progression include genetic factors, increasing age and nutrition. 3 Further targeting of the androgen receptor (AR) axis using novel therapeutics like abiraterone acetate and enzalutamide enhances survival for a limited time but also leads to resistance 4 emerging from the development of new substances. 2 However, ADT resistance occurs in a large number of patients within 2 to 3 years, is known as incurable metastatic castration-resistant PCa (mCRPC), and is associated with a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%